Is a mobile phone a disruptive innovation in the workplace? - Said, Mohd Fuaad; Adham, Khairul Akmaliah (Universitas Gadjah Mada, 2016)
Extant literature on technology adoption in the workplace generally analyses a single technology, thereby preventing us from a comprehensive understanding about the use of multiple technologies at work. As the usage of mobile devices becomes ubiquitous, knowing how the use of multiple technologies influence individual and group-related tasks is becoming more critical. Therefore, the objective of this study is to understand how managers perform their duties and functions and what technologies are utilized. This study adopts a qualitative study design by conducting in-depth interviews with eight managers employed in the public sector. We found four categories of convergence of mobile and fixed technologies in the workplace: supplementary, complementary, high-degree of integration, and full integration. The technology convergence is mainly influenced by the nature of the managerial work. Most importantly, mobile device is yet a disruptive innovation in the workplace, although its full integration with the fixed technology can be promoted.